2012
DOI: 10.1108/03055721211227291
|View full text |Cite
|
Sign up to set email alerts
|

The combinative effect of electronic open networks and closed interpersonal networks on knowledge creation in academic communities

Abstract: Purpose -This paper aims to develop and test a theoretical framework that examines the capacity of electronic open networks and closed interpersonal networks in building social capital and creating new knowledge. Specifically, this article aims to extend understanding in the field of knowledge management by examining how social networks can accumulate social capital and build up potential and absorptive capacity for the creation of new knowledge. Design/methodology/approach -The authors reviewed the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Hassanian et al (2015) stated that the dynamism of three social factor sub-domainseducators' positive comorbidity, students' positive comorbidity and colleagues' positive comorbiditysupported KC. Similarly, Sherif et al (2012) indicated that open electronic networks and closed interpersonal networks in universities played a significant role in acquiring and simulating new knowledge, as well as in communicating and utilizing that knowledge.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Hassanian et al (2015) stated that the dynamism of three social factor sub-domainseducators' positive comorbidity, students' positive comorbidity and colleagues' positive comorbiditysupported KC. Similarly, Sherif et al (2012) indicated that open electronic networks and closed interpersonal networks in universities played a significant role in acquiring and simulating new knowledge, as well as in communicating and utilizing that knowledge.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…For Yoo et al (2011), absorptive capacity enables relevant knowledge to be identified and ensures the flexibility necessary to integrate a variety of knowledge types and create innovative ways of thinking. Absorptive capacity is also best developed in open networks because acquisition and assimilation are facilitated by the structural and cognitive dimensions of social capital (Sherif et al, 2012). Thus, it is suggested that absorptive capacity plays a mediating role between the knowledge-collection and donation processes and organizational performance; thus, the following hypotheses are proposed:…”
mentioning
confidence: 99%
“…Transactive memory bridges personal knowing to collaborative memory knowledge and takes the object of knowledge and creates shared, interactive dynamic knowing (Maruta, 2012, pp. 37-40; Sherif et al , 2012, pp. 278-279 and pp.…”
Section: Discussion Of the Concepts For Applying Skills And Meta-skills To Manage Complexitymentioning
confidence: 99%